Achievement of the Mother's Role According to Mercer's Theory is related to the Readiness of Pregnant Women to Undergo Sectio Caesarea Operation - Sujono, Annisa Juliani; Yuswanto, Tri Johan Agus; Solikhah, Fitriana Kurniasari; Pertami, Sumirah Budi (JURNAL INFO KESEHATAN, 2024)
The prevalence of caesarean section (C-section) deliveries has risen to encompass over 1 in 5 births (21%) globally and is projected to increase to nearly one-third (29%) by 2030. With this growing trend, optimal patient preparation becomes essential for ensuring safe and successful outcomes. Patient preparation involves multiple aspects, including physical readiness, nutritional status, gastrointestinal and abdominal hygiene, surgical site shaving, personal hygiene, bladder emptying, preoperative exercises, mental preparation, and informed consent. Mental preparedness, in particular, is closely associated with achieving maternal role attainment, as described in Mercer’s theory. This study aimed to explore the significant relationship between maternal role attainment, based on Mercer's theory, and the readiness of pregnant women to undergo C-section surgery. A quantitative correlational research design was employed, involving a sample of 52 pregnant women scheduled for C-section surgery, selected using the Total Sampling technique. Maternal role attainment (independent variable) was assessed using a validated questionnaire, while surgical readiness (dependent variable) was measured using a readiness questionnaire that had undergone validity testing. Data were analyzed using the Spearman Rank Correlation test. The results revealed that 26 participants (50.0%) had achieved their maternal role, and 47 participants (90.4%) demonstrated readiness for C-section surgery. Statistical analysis indicated a significant positive relationship between maternal role attainment and surgical readiness, with a p-value of 0.03 (<0.05) and a correlation coefficient of 0.401, suggesting a moderate and positive correlation. The conclusion is there are relationship between maternal role attainment, based on Mercer's theory, and the readiness of pregnant women to undergo C-section surgery. These findings imply that the greater the maternal role attainment, the higher the readiness of pregnant women to undergo C-section surgery.